Review on Canine Chronic Enteropathy - Marwein, Sherry Carelyne; Rajesh, J. B.; Rose, Kh Thanila; Kar, Payel; Behera, S. K.; Tolenkhomba, T. C.; Sarma, K. (International Journal of Bio-resource and Stress Management, 2025)
A review of literature revealed that diarrhoea and vomition in dogs were frequent reasons for veterinarians to examine dogs, as well as an increase in the occurrence of canine gastrointestinal issues. CE is a set of chronic intestinal diseases distinguished by persistent or recurring clinical symptoms such as diarrhea, vomition, loss of weight, and appetite abnormalities. It is diagnosed after eliminating out other possible causes, such as parasites, infections, or other systemic disorders. Dogs with chronic enteropathy, a phrase that refers to variety of intestinal tract inflammatory disorders and intestinal diseases, independent of their etiology or pathogenesis which was a set of complexes, non-specific gastrointestinal (GI) disorders in dogs that had symptoms that last three weeks or more and were unrelated to other conditions has been reviewed. One of the most crucial aspects of treating this condition is controlling nutrition. Prebiotics help dogs absorb nutrients more effectively, reduce inflammation, and boost their immunological response by promoting a healthy gut microbiome. To fully utilize the potential of prebiotics and symbiotics in canine nutrition, collaboration among veterinarians, animal nutritionists, and researchers is required. CE is frequently a lifelong condition that requires continual management. Working closely with a veterinarian is essential for an accurate diagnosis and efficient treatment. Dietary management is an important aspect in managing many cases.Early diagnosis and treatment can help the dog’s quality of life.